Action of Ganoderma lucidum mycelial growth ﬁltrates on Erysiphe diﬀusa and embryotoxicity assessment in a chicken embryo model - Cruz, Mycheli P. da; Larentis, Lucas T.; Vismara, Edgar de S.; Vismara, Lilian de S.; Freitas, Patricia F. de; Mazaro, Sérgio M. (Acta Biologica Szegediensis, 2022)
This work aimed to evaluate the antimicrobial eﬀect of Ganoderma lucidum mycelial growth filtrates (MGF) on the phytopathogen Erysiphe diffusa and their potential eﬀects on the embryonic development of Gallus gallus. The antimicrobial activity was evaluated on E. diffusa spores by the microdilution broth method. To evaluate embryotoxic and teratogenic eﬀects, fertile eggs of G. gallus received injections of solutions containing the filtrates of G. lucidum through the air chamber. After three days of incubation, we opened the eggs and evaluated egg viability, embryo survival, malformation occurrence, embryonic staging and heart rate. Live embryos were prepared using whole mount technique and the morphological analysis was performed. We used the generalized linear model to fit embryotoxicity and teratogenicity data. We verified that G. lucidum MGF showed inhibitory activity in vitro against E. diffusa and the minimum inhibitory concentrations ranged from 5 to 10 mg/mL. We could also observe that the filtrates did not present embryotoxic or teratogenic eﬀects on the early embryonic development of G. gallus, but induced significant diﬀerences in the embryonic mean heart rate and on the stage of embryonic development.